Learning Organization Mechanism in E-Government Management Stage in Makassar City Government Organizational Scope (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to describe the learning organization mechanism in the stages of e-government management within the Makassar city government organization. The fact shows that most of an organization is not aware of the importance of building a learning culture (Schein, 1990). E-government has become a priority program of government agencies, both at the center and regions all over the world, who not only viewed as a project that became a trend among the government, but it leads to how to improve the accountability, this research was conducted in the city of makassar with the use of a qualitative approach to the research results, namely the Transformation of the organization is realized through the application of the mechanism of learning organization in the form of the creation of top management support, implementation of training and development of human resources competency-based, the development of feedback on all fronts as well as the provision and development of mis (Management Information System) within the framework of e-government. running an e-government utilize the information system management as a means of exchanging information and knowledge in both formal and informal by using social media, webmail, website and SMS service center.